(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
Data on 25 species of lichenized and lichenicolous fungi new to the Crimean Peninsula, collected during Czech and Ukrainian-Czech lichenological excursions in June 2006 and May 2007 respectively, are provided. Among them, Arthonia lecanorina (Almq.) R. Sant., A. nideri (J. Steiner) Clauzade, Diederich & Cl. Roux, A. punctella Nyl., Caloplaca furax Egea et Llimona, C. soralifera Vondrák & Hrouzek, C. veneris Cl. Roux & Nav.-Ros., Carbonea assimilis (Körber) Hafelner & Hertel, Catillaria aff. scotinodes (Nyl.) Coppins, Endococcus macrosporus (Arnold.) Nyl., E. ramalinarius (Lind.) D. Hawksw., Fuscidea gothoburgensis (H. Magn.) V. Wirth & Vĕzda, Lichinella cribellifera (Nyl) P.P. Moreno & Egea, Milospium graphideorum (Nyl.) D. Hawksw., Phaeospora lecanorae Eitner, Placidium pilosellum (Breuss) Breuss, Verrucaria biatorinaria Zehetl, and V. poeltiana Clauzade & Cl. Roux are new to Ukraine. Caloplaca irrubescens (Nyl. ex Arnold) Zahlbr., Lecanora rouxii S. Ekman & Tønsberg, Lichenothelia scopularia (Nyl.) D. Hawksw., Melanelia hepatizon (Ach.) A. Thell, Peltigera collina (Ach.) Schrad., Staurothele areolata (Ach.) Lettau, Stigmidium rouxianum Calatayud & Triebel and Zwackhiomyces coepulonus (Norm.) Grube & R. Sant. are new to Crimea.